[Job] locked and [un]loaded: The effect of the Affordable Care Act dependency mandate on reenlistment in the U.S. Army - Michael S. Kofoed; Wyatt J. Frasier (W.E. Upjohn Institute for Employment Research, 2019)
One concern with employer-based health insurance is job lock or the inability for employees to leave their current employment for better opportunities for fear of losing benefits. We use the implementation of the Affordable Care Act's dependency mandate as a natural experiment. Data from the United States Army overcome some limitations in previous studies including the ability to examine workers with fixed contract expiration dates, uniform pay, and health coverage. We find that the ACA decreased reenlistment rates by 3.13 percent for enlisted soldiers aged 23-25. We also find that younger veterans who leave the army are more likely to attend college. These findings show that the ACA reduced job lock and increased college-going.
Keywords: I13; J22; H56; 330; Affordable Care Act; Job Lock; Military Enlistment; GI Bill